2016
DOI: 10.4103/0253-7176.191379
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction among Females Receiving Psychotropic Medication: A Hospital-based Cross-sectional Study

Abstract: Background:Sexual dysfunction (SD) is a known adverse effect of psychotropic medications. Even though sexual difficulties are common among women; very few studies have been carried out in India.Objective:To study the prevalence and nature of SD among females receiving psychotropic medications and to compare the SD among female patients receiving antipsychotics and antidepressants.Materials and Methods:Female investigator conducted a hospital-based cross-sectional study on female patients visiting the psychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…[25] Shetageri VN et al found that Sexual Dysfunction was prevalent in more than 50% of female patients on psychotropic drugs. [26] Adverse sexual effects can be complex because there are several potentially overlapping etiologies, including sexual dysfunction associated with the underlying mood disorder. [27] Grover S, et al found that approximately one third of the patients receiving lithium experience sexual dysfunction, and it is associated with poor medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Shetageri VN et al found that Sexual Dysfunction was prevalent in more than 50% of female patients on psychotropic drugs. [26] Adverse sexual effects can be complex because there are several potentially overlapping etiologies, including sexual dysfunction associated with the underlying mood disorder. [27] Grover S, et al found that approximately one third of the patients receiving lithium experience sexual dysfunction, and it is associated with poor medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…21 In India, for women to disclose and discuss about the hindrances and distress that they experience pertaining to sexual dysfunctions is considered a taboo as a result of the male dominated society and puritanical mindset. 22 This could be one reason why epidemiological investigations regarding FSDs in India, particularly are scant. [23][24] A second reason for the limited focus on FSD as compared to those in males could be difficulty in appropriately measuring the dysfunction.…”
Section: Female Sexual Dysfunction In Schizophrenia-an Overviewmentioning
confidence: 99%
“…Even Indian researchers suggest that having a married female as an investigator is an asset in reducing the cultural barrier and encouraging female patients to be free in explaining their sexual difficulties. 17 So preferably opportunities should be provided for such facilities. And in our country, where public hospitals are crowded enough, provisions should be there for discussing these issues in privacy.…”
Section: Partmentioning
confidence: 99%